114k views
17 votes
What is the product?

3x³(2x² +4x+1)
O 2x +4Xô + xô
O
6x¹0+12x5+3x5
O 6x² + 12x6 +5
O 3x5+2x² + 4x+1

User MappaM
by
5.5k points

1 Answer

6 votes

Answer:

6x⁵+12x⁴+3x³

Explanation:

3x³(2x² + 4x + 1) = 3x³ × (2x² + 4x + 1)

therefore

3x³(2x² + 4x + 1) =

(3x³ × 2x²) + (3x³ × 4x) + (3x³ × 1)

*NOTE: for the brackets the multiplication law of indices is applied, i.e:

nª × n^b = n^a+b therefore

x³ × x² = x^3+2 = x⁵

x³ × x = x^3+1 = x⁴

x³ × x⁰ = x^3+0 = x³

*Note the quoeficents multiple each other, i.e:

3 × 2 = 6

3 × 4 = 12

3 × 1 = 3

so:

= 6x⁵ + 12x⁴ + 3x³

User Alex Moleiro
by
5.3k points